Substrate Stiffness Induces Neutrophil Extracellular Traps (NETs) Formation through Focal Adhesion Kinase Activation - Abaricia, Jefferson O. (Biomaterials, 2021)
Neutrophils predominate the early inflammatory response to tissue injury and implantation of biomaterials. Recent studies have shown that neutrophil activation can be regulated by mechanical cues such as stiffness or surface wettability; however, it is not known how neutrophils sense and respond to physical cues, particularly how they form neutrophil extracellular traps (NET formation). To examine this, we used polydimethylsiloxane (PDMS) substrates of varying physiologically relevant stiffness (0.2-32 kPa) and examined the response of murine neutrophils to untreated surfaces or to surfaces coated with various extracellular matrix proteins recognized by integrin heterodimers (collagen, fibronectin, laminin, vitronectin, synthetic RGD). Neutrophils on higher stiffness PDMS substrates had increased NET formation and higher secretion of pro-inflammatory cytokines and chemokines. Extracellular matrix protein coatings showed that fibronectin induced the most NET formation and this effect was stiffness dependent. Synthetic RGD peptides induced similar levels of NET formation and pro-inflammatory cytokine release than the full-length fibronectin protein. To determine if the observed NET formation in response to substrate stiffness required focal adhesion kinase (FAK) activity, which is down stream of integrin activation, FAK inhibitor PF-573228 was used. Inhibition of FAK using PF-573228 ablated the stiffness-dependent increase in NET formation and pro-inflammatory molecule secretion. These findings demonstrate that neutrophils regulate NET formation in response to physical and mechanical biomaterial cues and this process is regulated through integrin/FAK signaling.